The rhetoric of participation: A study of the planning and development of low-income human settlements in the province of KwaZulu-Natal - Kahn, Fazel; Kahn, Sultan; Govender, Jayanathan (Africanus: Journal of Development Studies, 2018)
Participation in South Africa is encouraged and institutionalized in a variety of processes at different levels of government. The right of citizens and their representatives to exchange views and influence decision making at the local governance sphere such as the right to be included in decision making on the local budget, planning and development processes, and service delivery matters, is embodied in a wide range of national policies. However in reality, participation praxis appears to be theoretical, unclear, superficial and at times a tool to exercise political hegemony at the local level. This paper examines the level of people's participation in the planning and development of low-income human settlements in three research localities in the province of KwaZulu-Natal. It highlights, contrary to policy mandates to create real opportunities for participation by ordinary citizens, what one may term "rhetoric" that best serves the hegemony of political actors.